2022
DOI: 10.26668/businessreview/2022.v7i4.e750
|View full text |Cite
|
Sign up to set email alerts
|

Brand Element: Exploring the Effect on City Branding

Abstract: Purpose:  This study evaluates the contribution of symbolic brand elements such as the destination name, logo, and tagline to forming a destination brand.   Theoretical framework: Branding is identified with a symbolic element in a product. In the context of destination branding, an emblem or logo promises a tourist experience that can be remembered and associated with a particular destination by tourists or visitors. (Mihalis Kavaratzis & Hatch, 2013)   … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(33 reference statements)
0
5
0
2
Order By: Relevance
“…The brand identity is a concept generated from a company responsible for developing various products with unique qualities and offering a sustainable competitive advantage. The city branding and image in the tourism industry are essential in developing an intention to visit, which leads to the visiting decision (Chan, Suryadipura, & Novel, 2022;Kusumawati, Rahayu, & Putra, 2022). The study also found that the brand identity positively influenced the visiting decisions.…”
Section: Theoretical Framework and Empirical Studiesmentioning
confidence: 77%
See 1 more Smart Citation
“…The brand identity is a concept generated from a company responsible for developing various products with unique qualities and offering a sustainable competitive advantage. The city branding and image in the tourism industry are essential in developing an intention to visit, which leads to the visiting decision (Chan, Suryadipura, & Novel, 2022;Kusumawati, Rahayu, & Putra, 2022). The study also found that the brand identity positively influenced the visiting decisions.…”
Section: Theoretical Framework and Empirical Studiesmentioning
confidence: 77%
“…The questionnaire was developed from several previous research findings. Measurements of the city branding, brand identity, brand image, visiting decisions were adapted from Chan et al (2022), Anholt (2011), Vijaranakorn &Shannon (2017), andHusna, Rini, &Sembiring (2018), respectively. This study performed an instrument testing before the final data analysis to test the data's validity, reliability, and normality.…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini disebabkan "Stunning Bandung" adalah brand yang diberikan oleh Kementerian Pariwisata Republik Indonesia, sehingga hubungannya lebih bersifat vertikal. Untuk menggaungkan slogan yang erat dengan identitas yang melekat pada kota agar dapat menjadi brand, maka diperlukan kolaborasi antara pelaku usaha, pemerintah dan seluruh pihak (Chan et al, 2021) serta komunikasi dan hubungan masyarakat (Christine & Setyanto, 2021), termasuk melalui media sosial (Ramadhani & Indradjati, 2023) Pada konteks pemasaran program pariwisata, konsep branding kota secara spesifik memfokuskan kota sebagai destinasi wisata (Zahrah, 2023;Anholt, 2006;Hankinson, 2004), sehingga branding kota memiliki tujuan untuk menarik kunjungan wisatawan (Chan et al, 2022) dalam meningkatkan pendapatan daerah dan kesejahteraan masyarakat melalui sektor pariwisata (Nawangsari & Suksmawati, 2019). Konsep brand kota pada konteks ini, dipengaruhi oleh kualitas daya tarik wisata serta pengalaman berwisata yang dirasakan oleh wisatawan (Miftahuddin et al, 2021) yang membentuk kepuasan dan loyalitas (Panjaitan, 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…Additionally, it is simple to recall, which enables visitors to return and suggest the place to others (Chan et al, 2022) The most crucial component of branding is product differentiation (Murphy, 1988).…”
Section: Theoretical Foundations and Research Backgroundmentioning
confidence: 99%